Analisis Penerapan Manajemen Risiko Pembiayaan Baitut Tamwil Muhammadiyah Bina Masyarakat Utama Bandar Lampung - Moh - Fakhrurozi; Warsiyah - - (Jurnal Ilmiah Ekonomi Islam, 2021)
BTM BiMU is a savings and loan cooperative and sharia financing which is a cooperative legal entity. BTM BiMU's business activities in the field of savings and loans and sharia financing face business risks that can disrupt its business continuity. The implementation of good risk management is very necessary so that the risks that may arise can be calculated early on. This study aims to determine the application of financing risk management at BTM BiMU in minimizing losses that may occur and to determine the suitability of the implementation of risk management with sharia principles. This research was conducted using a descriptive method with a qualitative approach. Based on the research conducted, it can be concluded that BTM BiMU has implemented financing risk management by making its own regulations and self-controlled by having SOPs on Lending which are carried out in accordance with applicable regulations. In implementing the precautionary principle, all parties involved in financing must implement 5C+1S properly. The provisions enforced at BTM BiMU are in accordance with sharia principles and organizationally have certified members of the Sharia Supervisory Board.